Metal catalyst-free N-allylation/alkylation of imidazole and benzimidazole with Morita–Baylis–Hillman (MBH) alcohols and acetates - Mhasni, Olfa; Bouajila, Jalloul; Rezgui, Farhat (Beilstein Journal of Organic Chemistry, 2023)
A highly α-regioselective N-nucleophilic allylic substitution of cyclic MBH alcohols and acetates with imidazole or benzimidazole, in toluene at reflux with an azeotropic distillation, was successfully carried out with no catalysts or additives, affording the corresponding N-substituted imidazole derivatives in good yields. On the other hand, in refluxing toluene or methanol, the aza-Michael addition of imidazole onto acyclic MBH alcohols was performed using DABCO as an additive, leading to the corresponding 1,4-adducts in 70–84% yields.
Keywords: allylic substitution; aza-Michael addition; imidazole; Morita–Baylis–Hillman